Sustainability in fashion and luxury marketing: Results, paradoxes and potentialities. Issue 2 (3rd April 2022) - Akrout, Houcine; Guercini, Simone
ABSTRACT: This guest editorial article introduces a special issue devoted to the results, paradoxes, and potentialities emerging from the growing interest within the marketing and management research in the sustainability of fashion and luxury companies. While there has been extensive discussion of the meaning and forms of sustainability in the literature, the consistency of the models and behaviors applied to sustainability adopted by companies, and the results achieved in a field as important as fashion and luxury marketing, have not been verified. The articles in the special issue are briefly discussed, with some conclusions about the main results emerging from the various research studies. The five articles in this special issue seek to contribute to research that systemizes new models and tools that may be useful for practitioners and marketing researchers working in this field.